Effect of a Global Pandemic on Adult and Pediatric Cochlear Implantation across the United States. Issue 2 (17th February 2023) - Marinelli, John P.; Nassiri, Ashley M.; Lohse, Christine M.; Driscoll, Colin L. W.; Neff, Brian A.; Carlson, Matthew L.
Abstract : Objective: To characterize the effect of the COVID-19 pandemic on national cochlear implantation utilization by age using inclusive cochlear implantation data from two manufacturers between 2015 and 2020. Study Design: Analysis of prospectively registered consecutive patient data from two major cochlear implant (CI) manufacturers in the United States. Patients: Children or adults who received CIs. Interventions: Cochlear implantation. Main Outcome Measures: Annual implantation utilization by age. Results: A total of 46, 804 patients received CIs from the two participating manufacturers between 2015 and 2020. The annual number of implant recipients increased significantly during the first 5 years of the study period for both children and adults, from a total of 6, 203 in 2015 to 9, 213 in 2019 ( p < 0.001). During 2020, there was a 13.1% drop in national cochlear implantation utilization across all ages compared with 2019, including a drop of 2.2% for those ≤3 years old, 3.8% for those 4–17 years old, 10.1% for those 18–64 years old, 16.6% for those 65–79 years old, and 22.5% for those ≥80 years old. In a multivariable linear regression model, the percent drop in CIs differed significantly by age-group ( p = 0.005). Conclusions: Especially in light of the prepandemic projected CI counts for 2020, the COVID-19 pandemic reduced national cochlear implantation utilization by over 15% among Medicare-aged patients and by almost 25% among those ≥80 years old, resulting in more than a 3-year setback in total annual CIs. Children were less affected, with those ≤3 years old experiencing minimal interruption during 2020.